2010
DOI: 10.2478/v10042-009-0062-7
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor FOXL2 in ovarian function and dysfunction.

Abstract: Abstract:The Blepharophimosis Ptosis Epicanthus-inversus Syndrome is a genetic disease characterized by complex eyelid malformations often associated with premature ovarian failure (POF). BPES is basically an autosomal dominant disease, due to mutations in the FOXL2 gene, which encodes a forkhead transcription factor. More than one hundred mutations of FOXL2 have been described to date. In agreement with the BPES phenotype, FOXL2 is expressed (though not exclusively) in the developing eyelids and in fetal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Although they serve 2 complementary and independent pathways, they cooperate in suppressing any male signals (mainly Sox9) [Nef and Vassalli, 2009;Schlessinger et al, 2010]. The role of Foxl2 in follicular development has been well characterized [De Baere et al, 2009]. Recently, it was shown that loss of Foxl2 function throughout life causes somatic reprogramming of the ovary, resulting in the gain of tes- [Uhlenhaut et al, 2009].…”
Section: Normal Gonadal Developmentmentioning
confidence: 99%
“…Although they serve 2 complementary and independent pathways, they cooperate in suppressing any male signals (mainly Sox9) [Nef and Vassalli, 2009;Schlessinger et al, 2010]. The role of Foxl2 in follicular development has been well characterized [De Baere et al, 2009]. Recently, it was shown that loss of Foxl2 function throughout life causes somatic reprogramming of the ovary, resulting in the gain of tes- [Uhlenhaut et al, 2009].…”
Section: Normal Gonadal Developmentmentioning
confidence: 99%
“…Within the ovary, FOXL2 has been shown to be essential for ovary development and function [8]. Germline FOXL2 mutations are present in blepharophimosis-ptosis-epicanthus inversus syndrome (BPES) patients, an autosomal dominant condition characterized by defects in eyelid development with (type I) or without (type II) premature ovarian failure [1,916]. BPES FOXL2 mutations can induce cytoplasmic mislocalization as well as cytoplasmic or nuclear aggregation [15,17], which most likely contributes to altered function in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has an important role in follicular development (8,9,12,13). Recent investigations suggest a wider spectrum of tissues in which FOXL2 is expressed such as pituitary, macrophages, blood reticulocytes, hepatocytes, colon and heart (14). Infertility has a different range in affected females of type I (15,16).…”
Section: Introductionmentioning
confidence: 99%